HYDRAULIC ELEVATOR INSTALLATION ESTIMATION FOR THE WATER SOURCE WELL SAND-PACK CLEANING UP - V. V. Ivashechkin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article offers design of a hydraulic elevator installation for cleaning up water-source wells of sand packs. It considerers the installation hydraulic circuit according to which the normal pump feeds the high-level tank water into the borehole through two parallel water lines. The water-jet line with washing nozzle for destroying the sand-pack and the supply pipe-line coupled with the operational nozzle of the hydraulic elevator containing the inlet and the supply pipelines for respectively intaking the hydromixture and removing it from the well. The paper adduces equations for fluid motion in the supply and the water-jet pipelines and offers expressions for evaluating the required heads in them. For determining water flow in the supply and the water-jet pipe lines the author proposes to employ graphical approach allowing finding the regime point in Q–H chart by means of building characteristics of the pump and the pipe-lines. For calculating the useful vertical head, supply and dimensions of the hydraulic elevator the article employs the equation of motion quantity with consistency admission of the motion quantity before and after mixing the flows in the hydraulic elevator. The suggested correlations for evaluating the hydraulic elevator efficiency determine the sand pack removal duration as function of its sizes and the ejected fluid flow rate. A hydraulic-elevator installation parameters estimation example illustrates removing a sand pack from a water-source borehole of 41 m deep and 150 mm diameter bored in the village of Uzla of Myadelsk region, of Minsk oblast. The working efficiency of a manufactured and laboratory tested engineering prototype of the hydraulic elevator installation was acknowledged in actual tests at the indicated borehole site. With application of graphical approach, the suggested for the hydraulic elevator installation parameters calculation procedure allows selecting, with given depth and the borehole diameter, the normal pump, diameters of the supply and the water-jet pipe lines. After that, calculating dimensions of the jet pump – hydraulic elevator and the supply pipe line, and performing analysis of efficiency and work out characteristics of the installation.